Phytochemical Screening of Mahogany (Swietenia mahogany) Secondary Extract Potential as COVID-19 Medication - Candra, Ifan Aulia; Hasibuan, Syahbudin; Khoir, Fastabiqul (Green Engineering Society, 2024)
Mahogany secondary metabolite is proven effective as lung disease medication, including COVID-19 through docking analysis. Therefore, this study aimed to identify total secondary metabolite from leaves, stem barks, and seeds of mahogany (Swietenia mahogany). The study was carried out using an experimental and descriptive method by observing the visual changes in the sample including color and foam formation, total levels of flavonoids, alkaloids, and saponins using Gas Chromatography and Mass Spectroscopy (GC-MS). Phytochemical analysis was analyzed to identify secondary metabolites namely flavonoids, alkaloids, tannins, triterpenoid saponins, and steroids. The results of the GC-MS analysis showed that mahogany seeds extract had the highest retention time, with a total of 46,484, containing alpha -D Glucopyranoside, 3-Penten-2-one, and gamma-Tocopherol. These compounds belonged to derivatives of flavonoids and saponins, serving as potential COVID-19 medication. The other were terpenoid, steroid, and fatty acid group compounds (alpha humulene, neophyte diene, n-hexadecanoic acid, 9- Octadecenoic acid, Octadecanoic acid, Squalene, and Stigmasterol). In conclusion, these identified compounds have the potential for COVID-19 medication due to their anti-inflammatory, antiviral, antimicrobial immunosuppressant, anticancer, and anti-asthma properties.